A Novel Antibody-Toxin Conjugate to Treat Mantle Cell Lymphoma - Rather, Gulam M.; Lin, Siang-Yo; Lin, Hongxia; Szekely, Zoltan; Bertino, Joseph R. (Frontiers in Oncology, 2019)
Matriptase is a transmembrane serine protease, synthesized as an inactive single-chain zymogen on the endoplasmic reticulum and transported to the plasma membrane. Matriptase is activated in different epithelial and some B-cell malignancies and changes its conformation and activity is inhibited mainly by its endogenous inhibitor HAI-1. Activated matriptase plays a key role in tumor initiation as well as tumor progression, including invasiveness and metastasis. To target the anti-mitotic toxin (monomethyl auristatin-E) to activated matriptase, a novel antibody to activated matriptase was coupled to this toxin via a valine-citrulline-PABA linker. In a previous study, this fully loaded antibody-toxin conjugate was found to be effective against triple negative breast cancer cell lines and xenografts, alone or in combination with cisplatin (23). In this study, we examined the anti-tumor effect of the antibody toxin conjugate (ADC) against activated matriptase positive mantle cell lymphoma cell lines (JeKo-1, Maver, Mino and Z138). This ADC was cytotoxic to these cell lines with IC50s between 5-14 µg/mL. The ADC also showed a dose dependent anti-tumor effect on the JeKo-1 xenograft in mice without toxicity.